A69: Lupus Nephritis and Autoantibody Characteristics of a Single Center Cohort of Male Pediatric SLE Patients. Issue 11 (March 2014) - Wenderfer, Scott E.; Canter, Debra; DeGuzman, Marietta; Muscal, Eyal
Abstract : Background/Purpose: Males represent 4–22% of all SLE patients, but it is unclear if gender should influence management. A number of studies of mostly adult patients suggest genetic, hormonal and environmental aspects of gender differences contribute to differences in presentation, clinical course and outcome, including a positive association between male gender and nephritis and a negative association with disease activity and outcome. While differences may exist, these findings are supported by limited evidence, particularly for children and adolescents with SLE. Methods: We retrospectively reviewed records of the nearly 200 pediatric SLE patients actively followed in the TCH rheumatology and renal clinics between 2011 and 2013 to identify males with SLE. Characteristic autoantibody features and renal disease were defined. Results: We identified 25 males (48% Hispanic, 16% Black, 16% Asian). The mean age of onset of disease was 11.5 ± 0.6 yo. Comorbid autoimmune diseases were identified in 46% of patients and 31% had a positive family history of autoimmune disease. Hypocomplementemia was seen at least once in 54% of patients. The cumulative incidence of positive autoantibodies included 50% anti‐dsDNA, 54% with antiphospholipid abs, 42% with anti‐RNP, 38% with anti‐Ro (SS‐A), 19% with anti‐Smith, 15% with anti‐La (SS‐B), and 8% with RF. Only 35% (9) of male SLE patients developed lupus nephritis (LN), the majority of whom had class IV lesions (77%). Class V lesions were seen in 3 patients, including one with mixed histopathology (IV/V). LN was a presenting symptom in all 9 patients. Of these, 33% had acute kidney injury and 22% had crescentic disease on biopsy. The proportion of boys with LN and anti‐dsDNA antibodies was not significantly different from boys without LN (66% vs. 50%, p = 0.67); however, a significantly higher proportion of boys with LN had anti‐RNP abs (77% vs. 29%, p = 0.04). Conclusion: Although SLE predominately affects females, males with SLE represent an important subset of patients about which little is known. In our male cohort, rates of autoantibody positivity were similar to those published for females, but rates of kidney invovlement seem lower than expected. In addition, autoantibody profiling may not be as useful in predicting kidney involvement in boys. Additional research is of upmost importance to improve the diagnosis, quality of care, and outcomes of male SLE patients.